The Utterances of Swear Word by Indonesian Boy in Tembung Village - Siti Aisyah; Mutia Sari Devi; Merlin Fauziah Rahma (Yayasan Literasi Sains Indonesia, 2024)
This study aimed to find out the kinds of swear word that the boy uttered and the reason why he uttered the swear words in Medan. The subject of this research is an Indonesian boy named RAS. He is 7 years old. This research used descriptive qualitative design. The data was taken from conversation of RAS. The conversation was taken from recording technique and observing technique. The research recorded and observed RAS while played with his friends. The result shows that There are four types of swear word that are found in RAS utterances. They are: Excretory Term (tai, kentut), Body function Term (kepala, pantat), Animal Term (monyet,anjing, babi), Death term (mati). Furthermore, there are three reasons why speakers utter swear words, among others: Power and Control, Humor, and Self- Expression. The findings emphasize that the context in which swearing occurs is essential in understanding why certain words are chosen and what purpose they serve in the conversation.